2015
DOI: 10.1007/s10824-015-9261-6
|View full text |Cite
|
Sign up to set email alerts
|

Participation in cultural activities: specification issues

Abstract: In this paper, we analyse the frequency of individual attendance at cultural events comparing two econometric specifications-the zero-inflated negative binomial (ZINB) count data model and the double-hurdle model. Moreover, we address in detail the effect of education and economic variables-hourly earnings and non-labour income-on cultural demand. We use the Spanish Time Use Survey (Encuesta de Empleo del Tiempo) 2002-2003 and focus on working-age adults, running separate estimates by gender. Our results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
3
0
15
Order By: Relevance
“…A higher educational level is related, in particular, to a greater propensity to participate in activities that generate individual and social benefi ts, such as cultural activities, sport, reading the press and reading books. These results are consistent with those previously found in the fi eld of Cultural Economics (Ateca Amestoy, 2010;Muñiz et al, 2011 and2017), and serve as a link between them and earlier studies in the fi eld of Economics of Education (Escardíbul, 2002;Calero et al, 2011;Fernández-Gutiérrez and Calero, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A higher educational level is related, in particular, to a greater propensity to participate in activities that generate individual and social benefi ts, such as cultural activities, sport, reading the press and reading books. These results are consistent with those previously found in the fi eld of Cultural Economics (Ateca Amestoy, 2010;Muñiz et al, 2011 and2017), and serve as a link between them and earlier studies in the fi eld of Economics of Education (Escardíbul, 2002;Calero et al, 2011;Fernández-Gutiérrez and Calero, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In other research, Muñiz, Rodríguez and Suárez (2011) found that education, in Spain, is positively associated with time spent on both cultural activities and sports (albeit the intensity of this effect is higher for cultural activities). In addition, Muñiz, Rodríguez and Suárez (2017) found that education is an important determinant of both the probability of participating and the frequency of participation in cultural activities.…”
Section: The Non-monetary Effects Of Education: An Overviewmentioning
confidence: 99%
“…Para determinar el grado de asociación entre ellas se calculan los coeficientes de contingencia y de correlación, que indican relaciones de dependencia moderadas a altas, pues en todos los casos sus valores son superiores a 0,45. Una opción para evitar los problemas asociados a la multicolinealidad, como la pérdida de precisión de los estimadores, es eliminar alguna de las variables correlacionadas y comparar la sensibilidad de los resultados, como hacen Muñiz et al (2017). Con este procedimiento se corre el riesgo de incurrir en el sesgo de variables omitidas.…”
Section: Análisis Descriptivounclassified
“…Con respecto a los individuos sin educación, las personas con un nivel educativo mayor que el de secundaria tienen mayor probabilidad de participación que las de niveles inferiores. E, igual que en los trabajos de Ateca (2009), Aguado y Palma (2012) y Muñiz et al (2017), se encuentra un efecto monótonamente creciente del nivel educativo, reflejado en el aumento del efecto marginal a medida que se avanza a niveles superiores; el mayor efecto marginal es el de posgrado (7,4%). La educación específica en artes y humanidades tiene el efecto positivo esperado: la probabilidad de asistencia de personas con título universitario en estas áreas es un 3,9% mayor.…”
Section: La Decisión De Asistirunclassified
“…This method has been also used by [28], who used data from two music festivals in South Africa to explore the determinants of ticket sales. A logistic regression model was used by [29] to identify the determinant factors of likelihood and frequency of attendance at performing arts events in Taiwan; and [22] mentions zero-inflated negative binomial regression as a participation model, which is also used by [4,30]. In turn, ref.…”
Section: Introductionmentioning
confidence: 99%